INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER SISWA DI ROUDHATUL ATHFAL SE-KABUPATEN OKI-SUMSEL - Siti Mujawaroh; Dedi Setiawan (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This study examines the internalization of Islamic religious education values in the formation of student character in Roudhatul Athfal throughout the OIC-South Sumatra Regency. The purpose of this research was to determine the internalization of Islamic religious education values in the formation of student character in Roudhatul Athfal throughout the OIC-South Sumatra Regency.This research uses qualitative descriptive methods. The primary data sources in this study are teachers and students of Roudhatul Athfal in OIC-South Sumatra Regency. The result of this study is the internalization of Islamic education values carried out in Roudhatul Athfal throughout the OIC-South Sumatra Regency in increasing students' religious observance including memorization activities, congregational dhuhur prayers, early learning and religious lecture activities. Internalization of Islamic education values in Roudhatul Athfal in OIC-South Sumatra Regency is very effective in increasing the observance of student worship, especially Roudhatul Athfal students in OIC-South Sumatra Regency.